Oxygen vacancy stabilized Bi2O2CO3 nanosheet for CO2 electroreduction at low overpotential enables energy efficient CO‐production of formate. Issue 3 (2nd November 2022) - Zhang, Yangyang; Chen, Yanxu; Liu, Rong; Wang, Xiaowen; Liu, Huanhuan; Zhu, Yin; Qian, Qizhu; Feng, Yafei; Cheng, Mingyu; Zhang, Genqiang
Abstract: Bismuth‐based electrocatalysts are promising candidates for electrochemical CO2 reduction to formate attributing to the accelerated formation of *OCHO intermediate, while the high‐energy consumption remains a major challenge for practicability. Herein, we present the ultrathin Bi2 O2 CO3 nanosheets with abundant oxygen vacancy ( Vo ‐BOC‐NS) reconstructed from S, N‐co‐doped bismuth oxides that can act as durable electrocatalyst for CO2 ‐to‐formate conversion with faradic efficiency (FEformate ) of >95%, partial current density of 286 mA cm −2 with energy efficiency of 73.8% at −0.62 V (vs. RHE) and low overpotential of 200 mV in a flow electrolyzer. The theoretical calculations decipher that the oxygen vacancy can optimize *OCOH adsorption/desorption for the accelerated conversion kinetics. The pair‐electrosynthesis tactic of formate co‐production can enable a superior FEformate of >90% at wide cell voltage of 2–3.3 V and total yield rate of 3742 μmol cm −2 h −1 at 3.3 V, suggesting great potential for future industrialization. Abstract : Cathodic Bi‐based electrocatalyst with abundant oxygen vacancy displays highly efficient electrochemical CO2 reduction reaction (CRR) activity toward producing formate coupling with anodic methanol oxidation reaction (MOR), which provides an energy‐efficient and economic strategy for exclusively producing formate. The pair‐electrosynthesis tactic of formate co‐production can enable a superior FEformate of >90% at wide cell voltage of 2–3.3 V and total yield rate of 3742 μmol cm −2 h −1 at 3.3 V, suggesting great potential for future industrialization.